LESSONS LEARNED IMPROVING PALLIATIVE CARE ACCESS THROUGH TECHNOLOGY (IMPACTT) IN NURSING HOMES. (11th November 2018) - Stephens, C; David, D; Hunt, L
Abstract: Nursing homes (NHs) are increasingly the site of death for older adults with serious illnesses, many of whom have unmet palliative care (PC) needs. Given PC workforce limitations, leveraging alternative approaches such as technology-based tools is critical to addressing these gaps. This session will provide an overview of key aspects in the development, technical feasibility testing and piloting of the Improving Palliative Care Access Through Technology(ImPAcTT) intervention. ImPAcTT is a novel telehealth PC intervention that leverages existing technologies to provide staff education; family outreach, engagement and support; care coordination; and resident symptom management and facilitation of goals-of-care discussion. Ms. Bui will present findings from 14 NHs about staff attitudes towards death. Results highlight staff concerns about meeting needs of dying residents, providing guidance to best target PC education/support. Ms. Wertz will present feasibility/acceptability findings from 6 telehealth visits with 19 residents, families, providers and staff demonstrating that PC telehealth is technically feasible and acceptable and provides an innovative opportunity to improve access to needed NH PC services/supports. Dr. Stephens will present preliminary pilot data from 2 NHs to assess the feasibility/acceptability of study design and procedures, and estimate the impact on symptom distress, advanced care planning, satisfaction, and acute care utilization. Lastly, Dr. David will use CFIR to discuss barriers and facilitators to pilot implementation of ImPAcTT and considerations moving forward for successful implementation in a large-scale trial. Dr. Hunt will reflect on the overarching themes of this body of work and discuss implications for NH PC telehealth research.